Uji Kuat Tekan Paving Block Menggunakan Campuran Tanah dan Kapur Dengan Alat Pemadat Modifikasi - Larasati, Diah; Iswan, Iswan; Setyanto, Setyanto (Universitas Lampung, 2016)
Paving blocks are widely used as a public building construction, especially for paving roads,yards, sidewalks, parking lots, etc. The use of materials such as paving block the main constituentof cement and sand is relatively expensive. So in this study will provide another alternative tousing a mixture of soil and lime.Soil samples tested were from Kota Baru, South Lampung, with variations in the levels of themixture used is 0%, 5%, 10%, 15%, and 20% and the curing time for 14 days, as well as with thetreatment without burning and burning which will then be tested compressive strength and waterabsorption.The results showed that the compressive strength occurs at the most optimal mix of 15% and adecline in a mixture of 20%. The addition of lime percentage ≤15% resulted in the addition ofcompressive strength of paving blocks, while the addition of lime percentage of 20% resulted in adecrease in the compressive strength of the paving blocks. The compressive strength withoutburning still not meet the specifications of SNI 03-0691-1996, while paving blocks with burningthe lime content of 15% is already included in the classification of the quality of D. Waterabsorption test values not meet the specifications of paving blocks SNI 03-0691-1996 whichranges from 3%-10%.Keywords : Paving block, kapur, kuat tekan, daya serap air